Pengisian Jabatan Pelaksana Tugas Kepala Kantor Urusan Agama menurut Peraturan Perundang-Undangan di Indonesia - Lastari, Suci; Hartati, Hartati; Syamsir, Syamsir (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
In organising the government administration system in Indonesia, it is known as the appointment of the Acting (Plt) Head of the Religious Affairs Office who is a Temporary Official because the Definitive Official has permanent obstacles. The position of Executive has a term of office of 3 months and can be extended for 3 months based on the mandate given by his Superior. Plt is not authorised to make decisions and/or strategic actions that have an impact on changes in legal status in aspects of personnel organisation and budget allocation. However, in filling the position of Acting Head of KUA, it is often done when there is a definitive vacancy due to the previous official's retirement, mutation, death, or dismissal. The appointment of Plt is a valid administrative solution as long as it is done by complying with the provisions of time and applicable authority. However, when the implementation of the filling of the Plt position deviates from the normative provisions, there are legal issues that need to receive serious attention. The regulations regarding the Acting Head of KUA are regulated based on the Regulation of the Minister of Religion Number 34 of 2016. However, this PMA does not explicitly regulate the mechanism of filling the position of Acting Head of KUA when there is a vacancy, so the regulation space refers to the general provisions that apply in state personnel and government administration provisions. Therefore, the internal regulations of the Ministry of Religion also play a role in filling the gaps in technical regulations related to the appointment of Executives in the field. The type of research used is normative juridis.